Repopulating hematopoietic stem cells from steady-state blood before and after ex vivo culture are enriched in the CD34(+)CD133(+)CXCR4(low) fraction - Lapostolle, Véronique (Haematologica, 2018)
The feasibility of ex vivo expansion allows us to consider the steady-state peripheral blood as an alternative source of hematopoietic stem progenitor cells for transplantation when growth factor-induced cell mobilization is contraindicated or inapplicable. Ex vivo expansion dramatically enhances the in vivo reconstituting cell population from steady-state blood. In order to investigate phenotype and the expression of homing molecules, the expression of CD34, CD133, CD90, CD45RA, CD26 and CD9 was determined on sorted CD34(+) cells according to CXCR4 (“neg”, “low” “bright”) and CD133 expression before and after ex vivo expansion. Hematopoietic stem cell activity was determined in vivo on the basis of hematopoietic repopulation of primary and secondary recipients - NSG immuno-deficient mice. In vivo reconstituting cells in the steady-state blood CD34(+) cell fraction before expansion belong to the CD133(+) population and are CXCR4(low) or, to a lesser extent, CXCR4(neg), while after ex vivo expansion they are contained only in the CD133(+)CXCR4(low) cells. The failure of the CXCR4(bright) population to engraft is probably due to the exclusive expression of CD26 by these cells. The limiting-dilution analysis showed that both repopulating cell number and individual proliferative capacity were enhanced by ex vivo expansion. Thus, steady-state peripheral blood cells exhibit a different phenotype compared to mobilized and cord blood cells, as well as to those issued from the bone marrow. These data represent the first phenotypic characterization of steady-state blood cells exhibiting short- and long-term hematopoietic reconstituting potential, which can be expanded ex vivo, a sine qua non for their subsequent use for transplantation.